1953
DOI: 10.1001/jama.1953.02940340018007
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Antisepsis in Surgery

Abstract: Clearing. Fifteen showed at least 50% improvement, and five were considered failures.Two patients showed a tendency to relapse while they were being treated with quinacrine. Neither showed a good initial response, and results of treatment in both were ultimately classified as failures. Two untoward

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1955
1955
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…This is an important omission; one relatively recent randomized controlled trial (RCT) demonstrated an important beneficial effect on wound infection rates if oral antibiotics had been administered with mechanical preparation, even in this modern era, in which all patients routinely receive potent parenteral antibiotics 14, 15. As was found in much earlier studies, administration of oral non absorbable antibiotics was associated with a reduced bacterial load in the stool, colonic mucosa, and subcutaneous fat at the site of incision, suggesting a cause and effect relationship with infectious complications 1, 2, 4, 5, 16–19. So far no RCT has compared a strategy of parenteral antibiotic only, without any kind of mechanical bowel prep, to one involving parenteral antibiotics and mechanical bowel prep followed by the administration of oral non absorbable antibiotics.…”
Section: Introductionsupporting
confidence: 63%
“…This is an important omission; one relatively recent randomized controlled trial (RCT) demonstrated an important beneficial effect on wound infection rates if oral antibiotics had been administered with mechanical preparation, even in this modern era, in which all patients routinely receive potent parenteral antibiotics 14, 15. As was found in much earlier studies, administration of oral non absorbable antibiotics was associated with a reduced bacterial load in the stool, colonic mucosa, and subcutaneous fat at the site of incision, suggesting a cause and effect relationship with infectious complications 1, 2, 4, 5, 16–19. So far no RCT has compared a strategy of parenteral antibiotic only, without any kind of mechanical bowel prep, to one involving parenteral antibiotics and mechanical bowel prep followed by the administration of oral non absorbable antibiotics.…”
Section: Introductionsupporting
confidence: 63%
“…Neomycin alone, or fortified with phthalylsulphathiazole or bacitracin, may be such an antiseptic (Fog, 1953(Fog, , 1954Poth, 1953;Anlyan et al, 1954). These, however, produce the most complete and prolonged bacterial vacuum so far known.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, preoperatively the patient received poorly absorbed antibiotics that would generate very high intraluminal concentrations of the drug, and this high intraluminal drug concentration would reduce the inoculum of microorganisms contaminating the surgical site to a sub-infective concentration. The concept was championed by Edgar Poth [16] and the idea of using an oral preoperative kanamycin was supported by Cohn [17]. Prospective randomized clinical evidence to support the use of preoperative oral antibiotics came from Washington et al [18] in a study where neomycin and tetracycline were shown to reduce surgical site infections from 43% in the placebo group to only 5% in the antibiotic group.…”
Section: The Antibiotic Bowel Preparationmentioning
confidence: 99%